Sr/Ca and Ba/Ca ratios support trophic partitioning within a Silurian conodont community from Gotland, Sweden - Terrill, David F.; Jarochowska, Emilia; Henderson, Charles M.; Shirley, Bryan; Bremer, Oskar (Paleobiology, 2022)
Conodonts were a highly diverse and abundant vertebrate group whose fossils are found in marine Paleozoic and Triassic strata around the world. They inhabited environments ranging from lagoons to open oceans and are represented by a wide variety of dental morphologies. Conodonts may have filled many different ecological niches and represent a significant proportion of nekton before the Devonian. Despite this, very little is known about trophic ecology of conodonts. While morphological diversity suggests a complex trophic structure within conodont communities, there is little evidence to support dietary niche partitioning among conodonts. We tested the hypothesis that individual conodont taxa occupied different trophic niches, using Sr/Ca and Ba/Ca ratios preserved in the dental elements of assemblages from Silurian strata of Gotland, Sweden. Sr/Ca and Ba/Ca have been shown to vary in vertebrate skeletal tissues depending on trophic positioning, although biological and environmental conditions can affect these ratios. Environmental influences were minimized by examining entire conodont communities from a tropical epeiric sea and by measuring strontium isotope ratios using thermal ionization mass spectrometry in the most metropolitan taxon (Ozarkodina confluens). Composition of white matter, a tissue unique to conodonts, was also analyzed using microprobe analysis, revealing significantly lower Sr concentrations than in surrounding lamellar tissue, suggesting taxon-specific histology should be considered when analyzing conodonts for geochemical data. Excluding taxa with highly variable quantities of white matter, the results show that each taxon preserves different Sr/Ca and Ba/Ca ratios with limited overlap, indicating variation in trophic positioning.
CRIS-Team Scopus Importer:2022-04-29